ANALISIS PENGARUH PROFITABILITAS DAN RISIKO TERHADAP MODAL KERJA BERSIH PADA PERUSAHAAN TEKSTIL DI BURSA EFEK INDONESIA - Anggarani, Dwi; Ficilia, Inarti (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
Proper management of working capital will result in a higher level of efficiency so it will increase corporate profits. Profitability can be improved by investing in more profitable assets, while the risk is measured by the probability of a firm to be in a state of technically insolvent. If we want to improve profitability, the risk also rises, and vice versa. It is necessary for the selection of the companys decision between profitability and risk. Profitability as measured by Return on Assets and Return on Investment. While the risk is measured by the Current Ratio, Current LiabilitiesRatio and Current Asset Ratio. Because the selection decision between profitability and risk, then it is necessary to know the influence the profitability and risk of the net working capital. To test the hypothesis about the effect of the independent variable (profitability and risk) to net working capital, this study usingmultiple regression analysis models with the Ordinary Least Square. This study uses a quantitative approach. The results of this study are: (1) Profitability and risk having negative effect significance to net working capital. (2)Profitability and risk of significantly influence and simultaneously to the net working capital. (3) Profitability and risk as an independent variable is able to influence the dependent variable in which the net working capital by 40 %. (4) There is no significant influence profitability and partially on net working capital. (5) The risk is significantly influence and partially on net working capital. (6) The risk is more dominant to bring effect on the net working capital rather than the profitability. Keywords: profitability, risk and net working capital.